IMPLEMENTATION OF LEGAL PROTECTION THE FAMOUS TRADEMARKS IKEA AND SEPHORA BRAND (TRADEMARK’S LAW PERSPECTIVE) - Sri Arlina; Anggraini Dwi Milandry (Jurnal Cendekia Hukum, 2022)
In Indonesia, there have been many disputes over famous trademarks which ended by the cancellation and deletion of registered. This research aimed to describe and find out about, first, the legal protection of the right of famous trademarks rights based on law trademarks and second, implementation the legal protection of the right of famous trademarks rights (MA decision study of IKEA and SEPHORA brand). This research used the normative juridical method with a statutory and a case approaches. The result of this research first is the legal protection of the right of famous trademarks rights based on based on law trademark uses a constitutive system. One of the rules governing the Protection of Famous Marks is regulated in Article 21 (1). Furthemore, the implementation of the legal protection on the right of famous trademark in the case of the IKEA trademarks constrained by the difference interpretation of Article by the Panel of Judges and resulted ended by famous trademarks are fail to be protected. Meanwhile in the case of the SEPHORA trademarks implementation of the legal protection of the right of famous have protected the trademarks.